2018
DOI: 10.1039/c7tc05554d
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles/PEDOT:PSS composite hole-injection layer for efficient organic light-emitting diodes

Abstract: High performance Alq3-based organic light emitting diodes are achieved by using magnetic nanoparticles/poly(3,4-ethylenedioxythiophene)/poly(styrenesulfonate) as the composite hole-injection layer through the advantageous combination of light-scattering, localized surface plasmon resonance and magnetic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…More recently, our group reported high performance OLEDs within a multifunctional solution‐processed composite hole‐injection layer (HIL) based on the blends of composite NPs and PEDOT:PSS (Fe 3 O 4 @G‐PEDOT : PSS, Fe 3 O 4 @SiO 2 ‐PEDOT : PSS and Fe 3 O 4 @Au‐PEDOT : PSS). By optimizing the concentrations of composite metallic NPs, the current efficiencies were increased by 38.2 % (for Fe 3 O 4 @G‐based and Fe 3 O 4 @Au‐based OLEDs) and 35.0 % (for Fe 3 O 4 @SiO 2 ‐contained OLED), respectively, as shown in Figure . The viewing angles of all OLEDs with composite HILs were widened due to the scattering effects of NPs, which were verified by the angular‐dependent EL spectra, reflection and transmission spectra and AFM.…”
Section: Application Of Metal‐containing Nanomaterials In Oledsmentioning
confidence: 58%
See 2 more Smart Citations
“…More recently, our group reported high performance OLEDs within a multifunctional solution‐processed composite hole‐injection layer (HIL) based on the blends of composite NPs and PEDOT:PSS (Fe 3 O 4 @G‐PEDOT : PSS, Fe 3 O 4 @SiO 2 ‐PEDOT : PSS and Fe 3 O 4 @Au‐PEDOT : PSS). By optimizing the concentrations of composite metallic NPs, the current efficiencies were increased by 38.2 % (for Fe 3 O 4 @G‐based and Fe 3 O 4 @Au‐based OLEDs) and 35.0 % (for Fe 3 O 4 @SiO 2 ‐contained OLED), respectively, as shown in Figure . The viewing angles of all OLEDs with composite HILs were widened due to the scattering effects of NPs, which were verified by the angular‐dependent EL spectra, reflection and transmission spectra and AFM.…”
Section: Application Of Metal‐containing Nanomaterials In Oledsmentioning
confidence: 58%
“…More recently, our group reported high performance OLEDs within a multifunctional solution-processed compo- Figure 20. [91] The viewing angles of all OLEDs with composite HILs were widened due to the scattering effects of NPs, which were verified by the angular-dependent EL spectra, reflection and transmission spectra and AFM. The measurements of hole-only devices indicated that the hole transport abilities of the Fe 3 O 4 @Au-PEDOT: PSS and Fe3O4@G-PEDOT: PSS composite HILs are better than that of the Fe3O4@SiO2-PEDOT: PSS composite HIL, because the work function of the Fe 3 O 4 @Au-PEDOT: PSS and Fe3O4@G-PEDOT: PSS composite HILs increased while the Fe3O4@SiO2-PEDOT: PSS composite HIL decreased, which was proved by the XPS measurement.…”
Section: Nanocomposites-based Oledsmentioning
confidence: 69%
See 1 more Smart Citation
“…New-generation organic light-emitting diodes (OLEDs) are promising candidates for future displays and solid-state lighting applications owing to their unique cost-effective, lightweight, and flexibility features ( Kee et al., 2018 , Zhang et al., 2017 , Pan et al., 2017 , Lian et al., 2018 ). More importantly, high-performance deep-blue materials, which have a Commission International de L'Eclairage (CIE) coordinate of CIE y < 0.10 and even match the blue standard with the CIE (x, y) coordinates at (0.15, 0.06) of European Broadcasting Union, can provide widened color gamut, which is crucial to full-color displays ( Wu et al., 2013 , Tang et al., 2015 , Tao et al., 2017 , Wada et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The reproducible and economical synthesis of anisotropic magnetite (Fe 3 O 4 ) nanoparticles (NPs) with narrow size distribution continues to be a topic of considerable interest owing to their unique magnetic properties 1 and numerous potential applications related to the biomedical, 2,3 catalysis, 4,5 environment, 6 light emitting device, 7 and sensing 8 fields. Anisotropic Fe 3 O 4 NPs offer two main advantages.…”
mentioning
confidence: 99%